STUDI TENTANG KEMAMPUAN SISWA SEMESTER KEDUA MTS THAMRIN YAHYA RAMBAH HILIR DALAM MEMAHAMI TEKS-TEKS BAHASA INGGRIS - Robiatul Khasanah; Effendy Gultom; M. Nababan ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study was aimed at finding out the ability of the second year students of MTs Thamrin Yahya in comprehending English texts; they are Descriptive text, Narrative text and Recount text. The researcher used cluster random sampling technique to determine the sample. The samples were 30second year students. The data were taken from the students’ scores in comprehending English Texts. To collect the data, the researcher constructed 30 questions to measure the students’ ability in comprehending English texts. The time allocation was 60 minutes. The result of the study revealed that the students’ mean score was 64.4 which indicated that the students were in good level of ability. The highest mean score was in finding meaning of difficult words and in finding types of text with the mean score of 66.7. The lowest mean score was in finding inferences with the means score of 51.13. Keywords: Students’ ability, Reading, Comprehension, English Texts